Accumulation and health risk of heavy metals in local and imported fish (rastrelliger kanagurta) sold in Shah Alam, Selangor / Nadiatul Syima Mohd Shahid [et al.] - Mohd Shahid, Nadiatul Syima; Abdul Rasid, Salmi; Azmi, Alia; Rajan, Shantakumari; Nazli, Siti Nurshahida (Universiti Teknologi MARA, Sabah, 2021)
Global aquatic ecosystems are becoming increasingly polluted with heavy metals posing health concerns associated with fish consumption. This study aims to determine the concentrations of cadmium (Cd) and lead (Pb) in local and imported fish (Rastrelliger kanagurta), and its potential human health risk. Total local and imported fish (60 samples) were randomly selected and purchased from ten different supermarkets in Shah Alam, Selangor. Cd and Pb concentrations were assessed by using dry ashing-acid digestion technique and analysed with atomic absorption spectrometry (AAS). The analytical results shows that the mean concentration of Cd in local and imported fish (Rastrelliger kanagurta) were 0.487 ± 0.25 mg/kg and 0.267 ± 0.11 mg/kg, respectively. The mean concentration of Pb in local fish was higher at 2.774 ± 1.46 mg/kg compared to the imported fish (1.482 ± 0.81 mg/kg). Further analysis indicated that there are significant differences (p < 0.05) for both Cd and Pb levels in local and imported fish (Rastrelliger kanagurta) sold within Selangor supermarkets. The concentration of Pb in local fish sold from supermarkets failed to comply with all the standards guidelines. The hazard quotient (HQ) used for health risk assessment of Pb and Cd was found to be < 1 (HQ < 1) for imported fish and potential risk for local fish (HQ > 1). The study reveals that the local fish are not totally safe for consumption and the pollution concentrations are on the borderline but can be treated.